Drying methods of duck blood: Changes in volatile components and physicochemical properties - Ji Yoon Cha; Yea-Ji Kim; Tae-Kyung Kim; Jaejoon Han; Yun-Sang Choi (Poultry Science)
This study investigated the physicochemical properties and volatile components of duck blood powder to determine its quality characteristics based on drying methods. The drying methods of duck blood samples used were freeze drying (FD), hot air drying (HD), spray drying (SD), and vacuum drying (VD). Duck blood powder treated with HD presented the lowest lightness and the highest carbonyl content. The VD-treated powder exhibited the highest water activity and redness. The composition of volatile compounds in duck blood varied based on the drying method, with VD presenting the highest total relative concentration but the least number of identified compounds. The most abundant compound was d-limonene, which was found in all the samples, followed by hexanal in VD and SD, p-xylene in FD, and trimethylamine in HD. Principal component analysis and heatmap analysis demonstrated that duck blood samples processed using different drying methods exhibited distinct volatile compound profiles, with HD, FD, SD, and VD samples associated with specific chemical groups. Multiple factor analysis revealed distinct correlations between drying methods and the physicochemical properties of duck blood, with VD samples showing higher water activity, aldehydes, and ketones, whereas HD samples exhibited increased carbonyl content and acids, highlighting the influence of heat on protein oxidation. VD method, therefore, presents excellent characteristics in terms of time and quality during the powdering process to increase the industrial utilization of duck blood. These findings provide valuable insights for the food industry, enabling the selection of appropriate drying methods that preserve the desired qualities of duck blood, thereby enhancing its commercial viability and potential application in a variety of food products.